Resistance to fracture in fixed dental prostheses over cemented and screw-retained implant-supported zirconia cantilevers in the anterior region: an in vitro study - Rues, Stefan; Kappel, Stefanie; Ruckes, Dorothee; Rammelsberg, Peter; Zenthöfer, Andreas (The international journal of oral & maxillofacial implants, 2020)
Stefan Rues, MSc/Stefanie Kappel, PhD, DDS/Dorothee Ruckes, BSc/Peter Rammelsberg, PhD, DDS/Andreas Zenthöfer, PhD, DDS: Purpose: To evaluate the resistance to fracture in cantilevered fixed dental prostheses (cFDPs) of single implant-supported - zirconia cantilevers in the anterior region. Materials and Methods: Thirty-two cemented and solely screw-retained cFDPs - consisting of an implant-supported crown replacing the central incisor and an attached cantilever unit in the position - of the lateral incisor in the maxilla were constructed by computer-aided design (CAD) and machined by computer-aided - manufacturing (CAM). For the cemented solution, a cFDP was designed on top of a customized abutment luted - to an adhesive base. For screw-retained cFDPs, abutment, cement gap, and restoration of the cementable design - were combined. All cFDPs were veneered manually on the facial side. Half of the samples underwent artificial aging - (thermocycling and chewing simulation) before fracture tests were conducted with loads applied to the pontic either - parallel to the implant axis (axial loading on the pontic) or tilted lingually by α = 45 degrees (oblique loading on the - pontic). Thus, there were eight groups differing in cFDP design, artificial aging, and load application (n = 8/group). If - fracture (Fu,total) occurred within the implant components, the adhesive base was replaced by a cast CoCr base, and the - cFDP’s fracture resistance (Fu,cFDP) was also determined. Using statistical analyses (SPSS 24, IBM), factors affecting fracture - resistance were identified. Results: Fu,total was mainly correlated to screw fractures and therefore not affected by cFDP - design. Oblique loading on the pontic (Fu,total = 231 N - 352 N), however, led to a significant (P < .001) decrease in ultimate - load compared with axial loading on the pontic (Fu,total = 611 N - 815 N). In relation to Fu,total, Fu,cFDP was approximately - twice as high for both loading conditions. Conclusion: When relating the results to maximum occlusal forces exerted - in the maxillary anterior region, single implant-supported cFDPs can be a viable restorative treatment option.
Gesehen am 04.06.2020